Does production diversity support dietary diversity? Evidence from pastoral and agro-pastoral households in West Pokot County, Kenya - Billy Okemer Ipara; David Jakinda Otieno; Willis Oluoch-Kosura; Angela Adhiambo Andago; Magnus Jirström; Heather Mackay; Fredrik Fernqvist; Elisabeth Rajala (Frontiers in Sustainable Food Systems)
Consumption of part of own-produced food is regarded as a sustainable approach to attaining dietary diversity and a pathway to improved food and nutrition security. However, empirical evidence on the relationship between production diversity and dietary diversity is inconclusive, with some studies demonstrating a positive relationship while others reveal conflicting results. Furthermore, this relationship has not been examined in pastoral contexts. We used data from 502 pastoral and agro-pastoral households in West Pokot County, Kenya, to assess the relationship between production indicators and household dietary diversity. Our results show that households with more diverse production had more diverse diets. Additionally, we find that nutritional awareness, engagement in off-farm enterprises, income, market participation, and location based on agro-ecological characteristics influence dietary diversity. Our findings suggest that more diverse crop-livestock systems appropriate to the agro-ecological conditions of West Pokot may be a strategy toward addressing the nutritional inadequacies experienced in the region. Further investigation of the wider implications of such a transition is suggested.